RESEARCH OF THE TRIBOLOGICAL PROPERTIES OF CAST SILUMIN АК15М3 - E. I. Marukovich; V. A. Kukareko; V. Yu. Stetsenko; V. Chekulaev; P. G. Sukhotsky (Литьë и металлургия, 2018)
A comparative study of the tribological properties of antifriction silumin casting АК15М3 and typical bronzes БрОЦС, БрОФ and БрАЖ at the friction in the lubricant-20A in a wide range of sliding velocities and pressures of the tests. The conclusion is made that the silumin АК15М3 can be used to replace anti-friction bronze type БрОЦС, БрОФ and БрАЖ in highly loaded friction units.